(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
The effectiveness of the sports training process largely depends on the correct planning of the means and methods of developing physical qualities throughout the year. Coaches and teachers should know well the main tools and methods of developing and improving the physical abilities of young athletes. In this case, coaches should correctly choose the optimal combination of tools and methods for improving physical qualities in relation to specific conditions.